Targeting Streptococcus pneumoniae UDP-glucose pyrophosphorylase (UGPase): in vitro validation of a putative inhibitor - Monica Sharma; Swati Sharma; Pallab Ray; Anuradha Chakraborti (AboutScience Srl, 2020)
Background: Genome plasticity of Streptococcus pneumoniae is responsible for the reduced efficacy of various antibiotics and capsular polysaccharide based vaccines. Therefore targets independent of capsular types are sought to control the pneumococcal pathogenicity. UcrDP-glucose pyrophosphorylase (UGPase) is one such desired candidate being responsible for the synthesis of UDP-glucose, a sugar-precursor in capsular biosynthesis and metabolic Leloir pathway. Being crucial to pneumococcal pathobiology, the effect of UGPase inhibition on virulence was evaluated in vitro. Methods: A putative inhibitor (UDP) was evaluated for effective inhibitory concentration in S. pneumoniae and A549 cells, its efficacy and toxicity. Effect of UDP on adherence and phagocytosis was measured in human respiratory epithelial (A549 and HEp-2) and macrophage (THP1 and J774.A.1) cell lines respectively. Results: A differential effective inhibitory concentration of UDP for UGPase inhibition was observed in S. pneumoniae and A549 cells i.e. 5 µM and 100 µM respectively. UDP treatments lowered percent cytotoxicity in pneumococcal infected monolayers and didn't exert adverse effects on viabilities. S. pneumoniae adherence to host cells was decreased significantly with UDP treatments. UDP induced the secretion of IL-1β, TNF-α, IL-6, and IL-8 and increased pneumococcal phagocytosis. Conclusion: Our study shows UDP mediated decrease in the virulence of S. pneumoniae and demonstrates UDP as an effective inhibitor of pneumococcal UGPase.